2016
DOI: 10.18632/oncotarget.12513
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics reveals ALK promote cell progress via RAS/JNK pathway in neuroblastoma

Abstract: Emerging evidence suggests receptor tyrosine kinase ALK as a promising therapeutic target in neuroblastoma. However, clinical trials reveal that a limited proportion of ALK-positive neuroblastoma patients experience clinical benefits from Crizotinib, a clinically approved specific inhibitor of ALK. The precise molecular mechanisms of aberrant ALK activity in neuroblastoma remain elusive, limiting the clinical application of ALK as a therapeutic target in neuroblastoma. Here, we describe a deep quantitative pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…Analysis of Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment confirmed that proteins with down-regulated phosphorylation sites were shared among other canonical RTK signaling pathways (Fig. 3D), in agreement with a previous study (31). In contrast, proteins with up-regulated sites were significantly associated with pathways related to axon guidance, prolactin signaling, regulation of actin cytoskeleton, and signaling related to the FoxO transcription factors (Fig.…”
Section: The Druggable Alk Phosphoproteome Identifies Alk-driven Phossupporting
confidence: 90%
See 2 more Smart Citations
“…Analysis of Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment confirmed that proteins with down-regulated phosphorylation sites were shared among other canonical RTK signaling pathways (Fig. 3D), in agreement with a previous study (31). In contrast, proteins with up-regulated sites were significantly associated with pathways related to axon guidance, prolactin signaling, regulation of actin cytoskeleton, and signaling related to the FoxO transcription factors (Fig.…”
Section: The Druggable Alk Phosphoproteome Identifies Alk-driven Phossupporting
confidence: 90%
“…S1C) combined with high-resolution liquid chromatography-tandem MS (LC-MS/MS). We reasoned that combining the quantitative proteomics analysis for three ALK-targeting TKIs (TAE684, LDK378, and crizotinib) and analyzing the overlapping effects on ALK signaling would help to control for off-targets and serve as a better readout for ALK signaling inhibition compared to the previously used single-treatment strategy (30,31). Moreover, we performed three triple-SILAC experiments, allowing us to measure the effect of each inhibitor in duplicate to obtain more robust insights into inhibitor-specific effects ( fig.…”
Section: Ipp Refines Aberrant Alk Signaling Network In Nb Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a phase I clinical trial evaluating the efficacy of crizotinib as a single-agent revealed unfavorable results in neuroblastoma patients [ 109 ]. Therefore, the proportion of ALK-positive neuroblastoma patients benefits from Crizotinib is limited [ 110 112 ]. ATRX was found to be mutated in approximately 50% of adolescent and young adults with neuroblastoma [ 28 , 92 ].…”
Section: Promising Therapeutic Targetsmentioning
confidence: 99%
“…Phosphoproteomics has also been used to study various oncogenic signaling pathways such as Ras signaling [10] and PI3K signaling [11]. It has been applied to study lung cancer [12,13], ovarian cancer [14], neuroblastoma [15,16], and many other cancer entities.…”
Section: Introductionmentioning
confidence: 99%